Instytucjonalne wsparcie zrównoważonego rozwoju wsi i terenów wiejskich - Nowak, Katarzyna (Institutional support for sustainable development in rural areas, 2007)
The institutional support for rural areas is the issue which needs theoretical studies. It is an essential condition for the practical realization of the conception of sustainable development in rural areas. The article presents in a concise way the most important institutions having an impact on the rural development that exist in European practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 385-393